2019
DOI: 10.1105/tpc.19.00444
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Kernel Reallocation of Proteins in Maize Depends on VP1-Mediated Scutellum Development and Nutrient Assimilation

Abstract: During maize (Zea mays) seed development, the endosperm functions as the major organ for storage of photoassimilate, serving to nourish the embryo. a-Zeins and globulins (GLBs) predominantly accumulate in the maize endosperm and embryo, respectively. Here, we show that suppression of a-zeins by RNA interference (aRNAi) in the endosperm results in more GLB1 being synthesized in the embryo, thereby markedly increasing the size and number of protein storage vacuoles. Glb genes are strongly expressed in the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 124 publications
0
25
0
Order By: Relevance
“…For analysis of zeins in immature kernels, endosperms were collected at 18 and 24 DAP, and ground in the lipid nitrogen into fine powder. The extraction and analysis of zein proteins was according to the standard method of our laboratory 42 . For assaying the total protein content, 60 mg of endosperm powder was used for measurement by the instrument of ELEMENTAR Rapid N exceed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis of zeins in immature kernels, endosperms were collected at 18 and 24 DAP, and ground in the lipid nitrogen into fine powder. The extraction and analysis of zein proteins was according to the standard method of our laboratory 42 . For assaying the total protein content, 60 mg of endosperm powder was used for measurement by the instrument of ELEMENTAR Rapid N exceed.…”
Section: Methodsmentioning
confidence: 99%
“…The nonzein protein extraction was according to the standard method of our laboratory 42 . Twenty μg of nonzein proteins were used for immunoblotting analysis following the manufacture’s protocol, (Bio-Rad, catalog number 162-0177).…”
Section: Methodsmentioning
confidence: 99%
“…OsVP1, a global regulator in the integrated seed maturation and germination developmental program, mediated the ABA response during mid-to late-phase embryogenesis [26][27][28]. Thus we performed immunoblot analysis and found that there was no signi cant difference in VP1 protein content at different stages of seed development between WR04-6 and SN9816 ( Fig.…”
Section: Az Anatomymentioning
confidence: 99%
“…② CDC2A (Nowack et al, 2006). ③ VP1 (Zheng et al, 2019). (D) Developmental coordination between embryo and endosperm.…”
Section: A B C Dmentioning
confidence: 99%
“…of endosperm through endosperm-embryo communication, likely the ABA signaling pathway. It regulates scutellum development, enlarges embryo nutrient-storage capacity, and consequently mediates nutrient remobilization from endosperm to embryo (Zheng et al, 2019).…”
Section: Regulation Of Endosperm Development By Embryomentioning
confidence: 99%